PENERAPAN SANKSI PIDANA TERHADAP PEMILIK TEMPAT PROSTITUSI DI KECAMATAN SIATAS BARITA KOTA TARUTUNG - Maria Hose Sihombing; Mexsasai Indra; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Prostitution is a social phenomenon where women sell themselves doing sexual acts as a livelihood. In this definition clearly stated the existence of self-selling as a "profession" or daily livelihood, by way of sexual relations. In this case the moral damage is seen when the community practices the ownership of a place of prostitution as a place for commercial sex workers or familiarly known as CSWs. The purpose of this study aims to determine law enforcement against owners of prostitution sites, to determine the impact of prostitution premises on the community and, to determine the inhibiting factors of law enforcement against owners of prostitution in Siatas Barita District, Tarutung City.In this study the authors use the method of sociological research that is research conducted directly at the location or object of research that wants to see the correlation between law and society, in this study the researchers directly conducted research.From the results of the research that the author did can be concluded, the first law enforcement against the owners of prostitution in the District Siatas Barita Tarutung City is limited to administrative sanctions. it does not make the place of prostitution stop operating until now. Law enforcement against owners of prostitution in the District of Siatas Barita Tarutung City is not based on the Criminal Code. While the Criminal Code has regulated the issue of prostitution as in Article 296 of the Criminal Code and 506 of the Criminal Code. secondly With the presence of prostitution has an impact on the insecurity of the people who live near the place of prostitution caused by many crimes. The three obstacles in carrying out law enforcement against the owners of prostitution places are, among others, the lack of public legal awareness which has implications for their disobedience to the law, due to the spread of information that raids or policing will be held more rapidly so that participation becomes an obstacle.The author's advice, first To the North Tapanuli District Police to carry out law enforcement in accordance with the Criminal Code. Secondly, the people of Tarutung City are expected to be more concerned with the problem of prostitution that is increasingly widespread. Keywords: Law Enforcement-Crime-Prostitution